2011
DOI: 10.1111/j.1745-4565.2010.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

MICROBIOLOGICAL QUALITY OF THE GHANAIAN VOLTA CLAM (GALATEA PARADOXA)

Abstract: Microbiological quality of the Ghanaian Volta clam (Galatea paradoxa) was assessed by fecal coliform and total aerobic bacteria counts. Polymerase chain reaction (PCR) with universal eubacterial 16S and 23S rDNA primers was also used to show the presence of bacteria in samples of the gut fluid and mantle tissues. The clams were found to be laden with potential pathogenic bacteria identified by conventional methods. Twenty bacteria species were isolated. They were Pseudomonas aeruginosa, Klebsiella ornithinolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Contaminated water also has implications for aquatic organisms such as clams, a common and inexpensive source of protein and livelihood for the communities at the Volta estuary. Adjei-Boateng et al ( 2009) and Amoah et al (2011) found that the clam Galatea paradoxa in these areas was highly contaminated with FCs, due to its capacity to accumulate up to five times the bacterial load in the surrounding water, through its filter feeding activities.…”
Section: Typical Water Pollution Problem Causes and Impactsmentioning
confidence: 99%
“…Contaminated water also has implications for aquatic organisms such as clams, a common and inexpensive source of protein and livelihood for the communities at the Volta estuary. Adjei-Boateng et al ( 2009) and Amoah et al (2011) found that the clam Galatea paradoxa in these areas was highly contaminated with FCs, due to its capacity to accumulate up to five times the bacterial load in the surrounding water, through its filter feeding activities.…”
Section: Typical Water Pollution Problem Causes and Impactsmentioning
confidence: 99%